Review of LoRaWAN: performance, key issues and future perspectives - Muhammad Naim Che Kamarudin; Afida Ayob; Aini Hussain; Shaheer Ansari; Maher. G. M. Abdolrasol; Mohamad Hanif Md Saad (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the last few years, the Low-powered wide area networks (LPWAN) have gained popularity and massively deployed, especially in smart cities and agriculture, due to their advantages, such as energy efficiency, extensive coverage, and low cost. The long-range wide area networks (LoRaWAN) protocol is a new technology. It attracts the attention of many research centers worldwide as it allows data transmission at a low cost across long distances. This article reviews the performance of LoRa and LoRaWAN for both investigations in indoor and outdoor environments. Moreover, a performance analysis of this technology is made by focusing on five main indicators, which are coverage, time on air (TOA), packet error rate (PER), received signal strength indication (RSSI), and signal-to-noise ratio (SNR) while considering technical characteristics is included. The investigation settings were divided into two categories: simulation and testbed in a real-world application. Consequently, a table of summary of indicators used by the researcher was made to make it easier for other researchers to find references for their topics relevant to this review. Next, the identified key issues and solutions are discussed in this review. The issues discussed significantly affect the performance of various monitoring technologies regarding energy management, quality of service, coverage, signal interference, and data handling. Finally, this review will discuss the future perspective, provide valuable suggestions for future research works, and lead toward improving current LoRaWAN technology.